How Did Long Terawan Berawan develop sixteen vowel phonemes? - Burkhardt, Jurgen Martin (University of Hawaii Press, 2016)
The Long Terawan Berawan system of vowel phonemes consists of one monophthong in the antepenult, schwa, and four monophthongs in the penult, i, ə, a, and u. However, the final syllable exhibits ten monophthongs (i, ĭ, e, ĕ, a, ă, u, ŭ, o, ŏ) and six diphthongs (əi, əu, ăi, ai, ău, au). The paper describes how the Long Terawan vowel phoneme system emerged from a Proto-Western Malayo-Polynesian system of four monophthongs (*i, *ə, *a, *u).